Identify manifestations of social alienation among university students in light of their use of Facebook: الاغتراب الاجتماعي لدى الشباب الجامعي في ظل استخدام الفيسبوك (Elmergib Journal of Human Sciences, 2026)
The study aims to identify manifestations of social alienation among university students in light of their use of Facebook. It also seeks to uncover the causes and factors that lead to this alienation, while monitoring the impact of Facebook on university students. The study relied on a descriptive analytical approach through a social survey of the sample, and reached several conclusions, the most important of which are as follows: A. Field studies have shown that one manifestation of social alienation is the use of Facebook as a means of maladjustment and non-integration into reality, as an escape from reality, and as a lack of alternatives for spending free time. This confirms social isolation as a manifestation of alienation and a feeling of meaninglessness..B. There are positive and negative effects of Facebook use, some of which are beneficial to study and others are not.C. The study showed that there are no statistically significant differences in the levels of social alienation among the sample individuals related to variables (gender, major, academic level. D. The study showed that there are statistically significant differences in the levels of social alienation among the sample individuals related to the variable (age group).
Keywords: Alienation; social; Facebook; youth; university